(The Role of Woman’s Shelters in Rehabilitation of Battered Women (An Study Applied in the Social Protection Institution in Jeddah - Al - Ghuraibi, Manal bin Ali bin Abdullah (Journal of Humanities & Social Sciences, 2018)
This study aimed to identify the dimensions of the phenomenon of domestic violence and to reveal the role of social protection (both the committee and the house) in the face of violence against women and to reveal the reality of the abuses after they left the social protection home. The study applied the case study approach, where the study used the interviews as a study tool. The sample of the study was 10 cases of women in the social protection house or those who were discharged from the social protection house. The most important results of the study were non-stop violence at the economic or educational level and the lack of programs that provide the classified works, the lack of social protection, lack of follow-up care efforts, and lack of cooperation between the state agencies concerned with combating violence. The most important recommendations were the intensification of courses for those working in this field, and providing women who were subject to violence to education and rehabilitation programs, as well as increasing the awareness of the members of the community and work on supporting efforts between the organs of the state concerned.